Strategi Pembelajaran Aktif untuk Meningkatkan Partispasi Siswa dalam Kegiatan Pembelajaran Pendidikan Agama Islam di UPTD SPF SDN Cibubukan: Active Learning Strategies to Enhance Student Participation in Islamic Religious Education at UPTD SPF SDN Cibubukan - Lidawati, Lidawati; Gayo, Lina (Abdurrauf Social Science, 2025)
Student participation in learning is a crucial factor in achieving optimal educational outcomes. However, in many elementary schools, including UPTD SDN Cibubukan, low student engagement in Islamic Religious Education (IRE) classes remains a challenge. This study aims to examine the effectiveness of active learning strategies in enhancing student participation in IRE at UPTD SDN Cibubukan. This research employs a qualitative approach with a case study design. Data were collected through classroom observations, interviews with teachers and students, and document analysis. The implementation of various innovative teaching methods, such as group discussions, problem-based learning (PBL), and educational games, was analyzed to assess their impact on student engagement. The findings indicate that active learning strategies significantly enhance student participation in IRE classes. Group discussions encourage students to share ideas, express opinions, and collaborate in problem-solving, thereby improving their understanding of the material while developing social and communication skills. The PBL method provides students with real-life scenarios that enhance their critical thinking and problem-solving abilities. Additionally, educational games create an enjoyable and interactive learning environment, increasing student motivation and participation. The results show a noticeable improvement in student engagement, as evidenced by an increased number of students asking and answering questions, actively participating in class discussions, and enthusiastically engaging in educational games. These findings confirm that active learning strategies are highly effective in fostering student involvement and motivation, ultimately contributing to better learning outcomes in Islamic Religious Education. [ Partisipasi siswa dalam pembelajaran merupakan faktor penting dalam mencapai hasil belajar yang optimal. Namun, rendahnya keterlibatan siswa dalam mata pelajaran Pendidikan Agama Islam (PAI) masih menjadi tantangan di banyak sekolah dasar, termasuk di UPTD SDN Cibubukan. Penelitian ini bertujuan untuk mengkaji efektivitas strategi pembelajaran aktif dalam meningkatkan partisipasi siswa dalam pembelajaran PAI di sekolah tersebut. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Pengumpulan data dilakukan melalui observasi kelas, wawancara dengan guru dan siswa, serta analisis dokumen. Implementasi berbagai metode pembelajaran inovatif, seperti diskusi kelompok, pembelajaran berbasis masalah (PBL), dan permainan edukatif, dianalisis untuk menilai dampaknya terhadap keterlibatan siswa. Hasil penelitian menunjukkan bahwa strategi pembelajaran aktif secara signifikan meningkatkan partisipasi siswa dalam pembelajaran PAI. Diskusi kelompok mendorong siswa untuk berbagi ide, mengemukakan pendapat, dan bekerja sama dalam menyelesaikan masalah, sehingga tidak hanya meningkatkan pemahaman mereka terhadap materi, tetapi juga mengembangkan keterampilan sosial dan komunikasi. Metode PBL memberikan kesempatan bagi siswa untuk menghadapi situasi nyata yang mendorong kemampuan berpikir kritis dan pemecahan masalah. Selain itu, permainan edukatif menciptakan suasana belajar yang menyenangkan dan interaktif, sehingga meningkatkan motivasi dan partisipasi siswa. Peningkatan partisipasi siswa terlihat jelas melalui tingginya jumlah siswa yang bertanya, menjawab pertanyaan, serta berpartisipasi aktif dalam diskusi kelas dan permainan edukatif. Hasil penelitian ini menegaskan bahwa strategi pembelajaran aktif terbukti sangat efektif dalam meningkatkan keterlibatan dan motivasi siswa, yang pada akhirnya berdampak positif terhadap hasil belajar mereka dalam Pendidikan Agama Islam].